Anaerobic digestion of fines from recovered paper processing – Influence of fiber source, lignin and ash content on biogas potential. (January 2016) - Steffen, Friedrich; Requejo, Ana; Ewald, Christian; Janzon, Ron; Saake, Bodo
Highlights: Fines fraction from recycled fiber had high ash and lignin content. Anaerobic digestion was not affected by inorganic compounds. Anaerobic conversion of carbohydrates was governed by substrates lignin content. Highest daily methane yield was obtained for fines from chemical pulps. Lignin-rich fines from mechanical pulps showed limited conversion rates. Abstract: Fines concentration harms paper machine runability and output quality in recovered paper processing, hence, their extraction would be fundamentally beneficial. In this study, separated fines from an industrial recycled fiber pulp (RFP) were characterized and evaluated for their potential biogas yields with a focus on understanding the role of varying lignin and ash contents. Further, these results were compared with biogas yields from conventional chemical and mechanical pulps. Overall, methane yields of fines from mechanical pulps (21–28 mL/gVS ) and RFP (127 mL/gVS ) are relatively low compared to the high methane yields of 375 mL/gVS from the chemical pulp fines. However, it was shown that the high ash content in RFP fines (up to 50%) did not negatively influence overall yield, rather, it was the presence of slowly biodegrading lignin-rich fiber fines.